PENGARUH BEBAN KERJA DAN LINGKUNGAN KERJA TERHADAP KEPUASAN KERJA KARYAWAN PADA PT HUTAHAEAN GROUP PEKANBARU - Simanullang, Marsauli; Karneli, Okta (Jurnal Daya Saing, 2024)
Abstract: This study aims to determine the influence of workload and work environment on employee job satisfaction at PT Hutahaean Group Pekanbaru. This research is a quantitative research with a descriptive approach. The population in this study is employees of PT Hutahaean Group Pekanbaru with a sample of 66 respondents. Data was collected through the distribution of questionnaires, and data analysis was carried out with the help of SPSS (Statistical Product And Service Solution). The results of this study show that workload has a negative and significant effect on job satisfaction, the work environment has a positive and significant effect on employee job satisfaction, and workload and work environment have a positive and significant effect on employee job satisfaction at PT Hutahaean Group Pekanbaru. Keywords: Workload, Work Environment, Job Satisfaction